2022
DOI: 10.3390/life12010075
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Cardiac Injury in COVID-19 Patients with Acute Ischaemic Stroke: What Do We Know So Far?—A Review of the Current Literature

Abstract: With the onset of the COVID-19 pandemic, it became apparent that, in addition to pulmonary infection, extrapulmonary manifestations such as cardiac injury and acute cerebrovascular events are frequent in patients infected with SARS-CoV-2, worsening clinical outcome. We reviewed the current literature on the pathophysiology of cardiac injury and its association with acute ischaemic stroke. Several hypotheses on heart and brain axis pathology in the context of stroke related to COVID-19 were identified. Taken to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Cardiovascular damage and immune dysregulation during the acute phase of COVID‐19 may result in an increased risk of long‐term CVD. 6 , 10 , 11 Several mechanisms and pathways have been suggested. Direct damage to the myocardium may occur via angiotensin‐converting enzyme 2 receptors, which facilitate entry of SARS‐CoV‐2, a strain of coronavirus causing COVID‐19, into host cells.…”
mentioning
confidence: 99%
“…Cardiovascular damage and immune dysregulation during the acute phase of COVID‐19 may result in an increased risk of long‐term CVD. 6 , 10 , 11 Several mechanisms and pathways have been suggested. Direct damage to the myocardium may occur via angiotensin‐converting enzyme 2 receptors, which facilitate entry of SARS‐CoV‐2, a strain of coronavirus causing COVID‐19, into host cells.…”
mentioning
confidence: 99%
“…In terms of cardiac examination, our data showed that the proportion of abnormal ECG (72.7 vs. 36.1, P < 0.05, Table 3) and hs-cTn level (0.80 ± 0.34 vs. 0.08 ± 0.03, P < 0.05, Table 2) in the END group were signi cantly higher than that in the Non-END group. Previous studies have con rmed that cardiac injury in patients with COVID-19 combined AIS is mainly associated with coagulation dysfunction, vascular endothelial injury, and microthrombosis induced by SARS-CoV-2 infection [13,14]. There was no signi cant difference between two groups in serum CK, CK-MB and LDH (Table 2).…”
Section: Resultsmentioning
confidence: 78%
“…Despite the absence of DAD in four cases, the role of SARS-CoV-2 in mortality cannot be ruled out, particularly in the cases with ACS and this issue could be viewed as a caveat in our stratification approach. This is evidenced by the previous studies linking COVID-19 with direct cardiac damage and indirect involvement through the thrombotic complications [ 55 ]. However, we are inclined to believe that the cases in the “death with SARS-CoV-2 infection” group did not pass away due to SARS-CoV-2 complications since the subjects in this group lacked co-morbidities and were younger compared to those with histopathologic evidence of death due to the infection.…”
Section: Discussionmentioning
confidence: 80%